Análisis de la estabilidad de una economía con desequilibrios sectoriales - Xesús Pereira López; José Luis Qui\~noá López; Melchor Fernández Fernández (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2013)
– The presence of negative values in the primary inputs vector in the input output framework has been considered as a limitation to the development of multi-sectoral linear models. It is true that, when this circumstance happens, the industries that are related appear unbalanced, however, the whole economic system could be stable within a short time. In this paper we demonstrate that this fact does not imply an error in the construction of the input-output tables nor involves unavoidable modifications to facilitate its use in modelling. It will be shown how non-negatives solutions can appear without taking into account the classic Hawkins-Simon condition. In other words, in this paper we examine until which extent sectoral imbalances do not put in danger the viability of the whole economic system under study. In line with this, we introduce several tools, as theorems, in order to see in which cases non-negatives Leontief's inverses can exist that enable the development and solution of supply and demand input-output models. It is also considered the possible economic interpretations of the different instrumental matrices used in the described analysis.
Keywords: C67; D57; 330; input-output; negative values; economic stability